Comparison of Simvastatin and Rosuvastatin in Oxidation and Antioxidant Levels in Male Rabbits Infected with Experimental Lipid Disorder - Maysam Ibrahim Mahdi Al-Naisani; Mostafa Ali Abdulrahman; Rafah Razooq Hameed (Tikrit Journal of Pure Science, 2019)
The study was carried out in the animal house of Samarra University, This study included evaluation of two drugs as antioxidants outside the body. As well as comparing the effect each of them on oxidation and antioxidant of infected male rabbits with experimental lipid disorder by treated them with Triton x100. The 48 domestic rabbits were used, divided into 6 groups and each group containing 8 rabbits. The level of oxidation and antioxidant was measured malondialdihyde, peroxy nitrite and ceroplasmin. The results showed that simvastatin has a high antioxidant capacity compared with rosuvastatin which has a lower susceptibility to the standard substance (vitamin C). The results showed a significant increase of P≤0.05 in the concentration of malon dialdehyde and peroxy nitrite, and a significant decrease P≤0.05 in the concentration of ceroplasmin in the serum of the infected group, also the results showed a significant decrease P≤0.05 in malon dialdehyde in the serum of all groups compared to the infected group. The fifth group which was treated with rosuvastatin demonstrated a significant decrease P≤0.05 in malon dialdehyde compared with the other groups. The results exhibited a significant decrease P≤0.05 in the concentration of pyroxy nitrite root in the serum of all groups compared to the infected group without significant differences. The results showed a significant increase of P≤0.05 in ceroplasmin concentration in the serum of all groups compared with the infected group.